2007
DOI: 10.1097/mlg.0b013e318145388f
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Smoking on Short‐Term Quality of Life Outcomes in Sinus Surgery

Abstract: This study confirms that smokers and nonsmokers achieve a highly significant short-term benefit from endoscopic sinus surgery using a clinically-validated symptom severity scale in a prospective study. Interestingly, smokers achieved a greater short-term benefit than nonsmokers did. This study calls into question the notion that current smokers are poorer candidates for endoscopic sinus surgery. Further prospective studies to confirm these results and provide long-term analysis should be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 13 publications
1
40
2
1
Order By: Relevance
“…Several studies have suggested that smokers have worse outcomes after functional endoscopic sinus surgery (FESS) when compared to nonsmokers, including a higher revision rate for smokers compared to nonsmokers, smoking as a significant factor in reasons for revision surgery, decreased postoperative endoscopic scores in smokers, increased revision rates in children exposed to secondhand smoke and worse long-term 20-item sinonasal outcomes test (SNOT-20) scores in smokers [13,14,15,16,17]. Our data previously published in ‘The effects of smoking on short-term quality of life outcomes in sinus surgery' [18] demonstrated that smokers actually achieved greater short-term benefits compared to nonsmokers. This was further investigated in our study ‘Effects of smoking on quality of life following sinus surgery: 4-year follow-up' [19], which also showed that both smokers and nonsmokers continued to maintain similar improvements in SNOT-20 scores.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Several studies have suggested that smokers have worse outcomes after functional endoscopic sinus surgery (FESS) when compared to nonsmokers, including a higher revision rate for smokers compared to nonsmokers, smoking as a significant factor in reasons for revision surgery, decreased postoperative endoscopic scores in smokers, increased revision rates in children exposed to secondhand smoke and worse long-term 20-item sinonasal outcomes test (SNOT-20) scores in smokers [13,14,15,16,17]. Our data previously published in ‘The effects of smoking on short-term quality of life outcomes in sinus surgery' [18] demonstrated that smokers actually achieved greater short-term benefits compared to nonsmokers. This was further investigated in our study ‘Effects of smoking on quality of life following sinus surgery: 4-year follow-up' [19], which also showed that both smokers and nonsmokers continued to maintain similar improvements in SNOT-20 scores.…”
Section: Introductionmentioning
confidence: 71%
“…While these current studies demonstrate that passive and active smoking contribute to CRS, long-term results on smoking after FESS have not been sufficiently evaluated [20]. Our previously published data show that smokers actually have similar if not improved quality of life scores compared to nonsmokers and that smoke-induced CRS may represent a different subset of disease [18,19,20]. The present study showed a trend towards an increased prevalence of nasal polyposis and revision surgery in the nonsmoking group, although these findings did not reach statistical significance (p = 0.107 and 0.45, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, current CS has been associated with nasal discharge and blockage [25], reduced perception of smell [7], and snoring and sleep apnoea [8,26,27], as well as headache [28], coughing [29], and sinusitis and sinus problems [30], although several studies have not been able to identify similar associations [10][11][12][13]15]. A doseresponse like relationship between CS and upper respiratory conditions such as rhinitis, impaired olfaction, and sleep disturbances has also been described [26,31,32].…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, little information is currently available on the impact of CS on upper airway health. The habit has been associated with upper respiratory symptoms and disorders [6][7][8][9]; however, data is sparse and to some extent conflicting [10][11][12][13][14][15]. Further, studies examining the role of CS in subjects with persisting upper respiratory complaints are lacking.…”
Section: Introductionmentioning
confidence: 99%